Nonhuman gamblers: lessons from rodents, primates, and robots - Paglieri, Fabio; Addessi, Elsa; De Petrillo, Francesca; Laviola, Giovanni; Mirolli, Marco; Parisi, Domenico; Petrosino, Giancarlo; Ventricelli, Marialba; Zoratto, Francesca; Adriani, Walter (Frontiers in Behavioral Neuroscience, 2014)
The search for neuronal and psychological underpinnings of pathological gambling in humans would benefit from investigating related phenomena also outside of our species. In this paper, we present a survey of studies in three widely different populations of agents, namely rodents, non-human primates, and robots. Each of these populations offer valuable and complementary insights on the topic, as the literature demonstrates. In addition, we highlight the deep and complex connections between relevant results across these different areas of research (i.e., cognitive and computational neuroscience, neuroethology, cognitive primatology, neuropsychiatry, evolutionary robotics), to make the case for a greater degree of methodological integration in future studies on pathological gambling.